The Dynamics of School Environment and the Impact of Parental Attention on the Academic Achievement of Students at SMA Negeri 1 Ketapang Sampang - Umroh, Umroh; Darmawan, Didit (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2024)
In the current era of globalization, students are faced with demands to consider the factors that influence the achievement of their learning outcomes. This research aims to reveal the role of an effective school environment and parental attention in improving the quality of student education. Quantitative methods were used in this research. In this research, this approach was chosen to provide a more measurable understanding of the role of the school environment and parental attention on student learning outcomes. The research population includes all students of SMA Negeri 1 Ketapang Sampang so that the research results can be more generally applied to this group. The use of multiple linear regression as a data analysis tool allows researchers to understand the extent to which certain variables, such as school environment and parental attention, contribute to variability in student learning outcomes. The findings show that the school environment has a fairly large role in determining student learning outcomes. Apart from that, emotional involvement and parental support also play a role in developing student academic achievement. With a school environment that supports learning and positive contributions from parents, it is hoped that student learning outcomes will improve.